Identification of 5‘ and 3‘ sequences involved in the regulation of transcription of the human mdr1 gene in vivo. - Mary Madden; Charles S. Morrow; Masayuki Nakagawa; Merrill E. Goldsmith; C.R. Fairchild; Kenneth H. Cowan (1993)
The human mdrl gene encodes a putative drug efflux pump (P-glycoprotein) whose overexpression is associated with the development of multidrug resistance (MDR).The promoter and 5"flanking DNA of this gene were isolated from a human genomic DNA library and used to prepare a series of chloramphenicol acetyltransferase (CAT) fusion vectors under the transcriptional control of the mdrl promoter (mdrCAT vectors).Transient transfection of these mdrCAT vectors produced CAT activities similar to those produced by transfection of CAT vectors containing viral promoters.The regulation of mdrl expression was examined in two MDR tumor cell lines selected for resistance to doxorubicin and their corresponding parental cell lines.Although nuclear run-on analysis indicates that the expression of the mdrl gene in these two MDR cell lines is regulated by transcriptional mechanisms, mdrCAT expression was not significantly increased in either of these lines relative to parental cells.Thus, the sequences involved in the transcriptional regulation in these cells are apparently not included in the constructs studied (-4741 to +286).Analyses of a series of deletion constructs show that the basal mdrl promoter activity is encoded by sequences that span a region adjacent to the transcription start site (-134 to +286) and that sequences 3' to the start of mdrl transcription are necessary for proper initiation of transcription in vivo.Structural and functional studies indicate that an initiator (Inr) sequence surrounding the major transcription start site governs accurate initiation of mdrl transcription.The human mdrl gene encodes a high molecular weight membrane protein which is commonly referred to as P-glycoprotein (Endicott and Ling, 1989).Overexpression of this